El pago parcial como causal de contradicción en las demandas de obligación de dar suma de dinero - Lara Vargas, Luis Angel Rodrigo (2019)
The thesis entitled "PAYMENT AS A CAUSE OF CONTRADICTION IN DEMANDS OF OBLIGATION TO GIVE SUM OF MONEY" intends to raise solutions on the problematic environment to the causes of contradiction in the processes of obligation to give sum of money initiated in the single process of execution, which are classified in article 690°-D of our Code of Civil Procedure, whereas, at present, such legal provision prescribes that if the defendant or the executed person bases his defence on a ground other than those prescribed by the rule in question, it shall be inadvertently rejected by the judge of the case, restricting the right of defence of the executed person only to the grounds of contradiction referred to above. In view of this situation, there is a clear picture of a violation of the right of defence of the person executed, where, in the contradictory, he is prevented from submitting authoritative documents indicating that the amount payable by the creditor differs from the amount actually due; as partial payments accepted by the creditor could have been made. This being the case, it is imperative and necessary to regulate a new ground of contradiction which will enable the executed person to validly exercise his right of defence and thereby to equalize the legal procedural relationship, so as not to be prejudiced by the charging of an excessive amount that may be harmful to you.